Effect of Dy3+-Cu2+ doping on structural, magnetic and electromagnetic properties of Co2Y-type hexaferrite. Issue 10 (15th May 2023) - Mohammed, Ibrahim; Mohammed, J.; Carol T, Tchouank Tekou; Srivastava, A.K.
Abstract: This study investigates the impact of the Dy 3+ -Cu 2+ doping on the structural, magnetic, and electromagnetic properties of Sr1.7 Ba0.3 Co2-x Dyx Fe12-x Cux O22 (x = 0.0, 0.1, 0.2) synthesized using sol-gel auto combustion. Rietveld refinement of the X-ray diffraction (XRD) data confirmed the single-phase formation of Co2 –Y-type hexaferrite. The lattice parameter a increased from 5.843 Å (x = 0.0) to 5.876 Å (x = 0.2) and c from 43.348 (x = 0.0) Å to 43.535 Å (x = 0.2). Fourier transform infrared spectroscopy (FTIR) identifies two absorption bands of hexagonal ferrites at 434 cm −1 and 553 cm −1 . The average grain size obtained from field emission scanning electron microscopy (FESEM) decreases from 2.47 to 1.83 μm. M − H loop obtained from the vibrating sample magnetometer (VSM) exhibited a saturation magnetization and coercivity of 31.80 emu/g, 38.60 emu/g, 41.60 emu/g, and 185.04 Oe, 335.16 Oe, 604.55 Oe with x = 0.0, 0.1, 0.2 respectively. According to the vector network analyzer (VNA) result, the minimum reflection loss of the Dy 3+ -Cu 2+ substituted Co2 –Y-type hexaferrite with 3.5 mm thickness was −18 dB at 9.4 GHz and bandwidth extending from 8.5 to 10 GHz. In summary, Dy 3+ -Cu 2+ substituted Co2 –Y-type hexaferrite has potential application in the X bands. Graphical abstract: Image 1